Topical and Systemic Fluorides in Children with Renal Diseases - POLICY STATEMENT, FDI; PTS, Stanowisko (Journal of Stomatology, 2015)
Following the ingestion of fluoride approximately 50% is normally excreted through the kidneys within 24 hours and most of the remainder is taken up by calcified tissues such as bones and teeth. Patients with renal dysfunction and especially young children may have an increased requirement for water intake. However there is no evidence of any risks to children with renal disease from fluoride at the doses recommended for the fluoridation of water supplies.